White matter integrity and processing speed in sickle cell anemia. (5th June 2018) - Stotesbury, Hanne; Kirkham, Fenella J.; Kölbel, Melanie; Balfour, Philippa; Clayden, Jonathan D.; Sahota, Sati; Sakaria, Simrat; Saunders, Dawn E.; Howard, Jo; Kesse-Adu, Rachel; Inusa, Baba; Pelidis, Maria; et al.
Abstract : Objective: The purpose of this retrospective cross-sectional study was to investigate whether changes in white matter integrity are related to slower processing speed in sickle cell anemia. Methods: Thirty-seven patients with silent cerebral infarction, 46 patients with normal MRI, and 32 sibling controls (age range 8–37 years) underwent cognitive assessment using the Wechsler scales and 3-tesla MRI. Tract-based spatial statistics analyses of diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI) parameters were performed. Results: Processing speed index (PSI) was lower in patients than controls by 9.34 points (95% confidence interval: 4.635–14.855, p = 0.0003). Full Scale IQ was lower by 4.14 scaled points (95% confidence interval: −1.066 to 9.551, p = 0.1), but this difference was abolished when PSI was included as a covariate ( p = 0.18). There were no differences in cognition between patients with and without silent cerebral infarction, and both groups had lower PSI than controls (both p < 0.001). In patients, arterial oxygen content, socioeconomic status, age, and male sex were identified as predictors of PSI, and correlations were found between PSI and DTI scalars (fractional anisotropy r = 0.614, p < 0.00001; r = −0.457, p < 0.00001; mean diffusivity r = −0.341, p = 0.0016; radial diffusivity r = −0.457, p < 0.00001) and NODDI parameters (intracellular volume fraction r = 0.364, p = 0.0007) in widespread regions. Conclusion: Our results extend previous reports of impairment that is independent of presence of infarction and may worsen with age. We identify processing speed as a vulnerable domain, with deficits potentially mediating difficulties across other domains, and provide evidence that reduced processing speed is related to the integrity of normal-appearing white matter using microstructure parameters from DTI and NODDI.